Effects of morphotropic phase boundary on the electric behavior of Er/Ti co-doped BiFeO3 ceramics. (1st January 2019) - Zhang, Liwei; Ke, Hua; Zhang, Hongjun; Li, Fangzhe; Zhao, Jinggeng; Luo, Huijiadai; Cao, Lu; Zeng, Gang; Li, Xiening; Wang, Wen; Jia, Dechang; Zhou, Yu
Abstract: Morphotropic phase boundaries (MPB) consisting of rhombohedral and orthorhombic phases formed within the range of 0.1 ≤ x ≤ 0.15 in Bi1- x Er x Fe0.97 Ti0.03 O3 ceramics. Orthorhombic phase transition was verified by the appearance of a new mode at 310 cm −1 in Raman spectra. Bridging phases as intermedia phases of MPB were rare in Bi1- x Er x Fe0.97 Ti0.03 O3 . Polarization and permittivity improved at MPB. Moreover, impedance spectroscopy revealed additional arcs with a distinct small polaron conduction mechanism. Er 3+ ions enhanced magnetic properties and induced a permittivity change at Neel temperature. The magnetodielectric effect resulted in a permittivity change rate of 1% at 10000 Oe. Graphical abstract: Unlabelled Image